THE BERRIASIAN SECTION IN THE BEL'BEK RIVER BASIN, SOUTHWESTERN CRIMEA - Yanin B.T.; Baraboshkin E.Yu. (My University, 2000)
The Berriasian section outcropping in the right-hand side of the Bel'bek River valley (southwestern Crimea) is described. The lithological and paleontological characteristics of 10 members recognized in the section are given. The proposed new scheme of subdivision of the Berriasian in the Bel'bek section includes the following ammonite zones and beds (from the base upward): Dalmasiceras crassicostatum Zone (lower Berriasian), Weberithyris moisseevi and Megadiceras koinautense beds (upper Berriasian), and the overlying Thurmanniceras pertransiensis Zone (lower Valanginian).
Keywords: Berriasian; Mesozoic::Cretaceous::Lower::Berriasian; Мезозой::Меловая::Нижний::Берриасский